To study high performance analysis of surround gate SOI MOSFET - Ashaf, Arjimand; Tyagi, Manisha; Mani, Prashant (International Journal of Engineering and Technology, 2018)
In this paper, we are presenting a rigorous study about SOI MOSFET devices development. The development of SOI devices based on gate structure from single gate to surround gate is presented in this paper. We compared the various electrical characteristics between Single gate, double gate, and bulk and also discussed the device modeling based on surround gate structure.